Bacillus amyloliquefaciens SQ-2 and Biochar: A Promising Combination for Enhancing Rice Growth in Pb/Al-Contaminated Acidic Soils - Guohui Gao; Xue Li; Jiajun Ma; Yumeng Cui; Ming Ying; Lei Huang; Meitong Li (Microorganisms, 2025)
In this study, Bacillus amyloliquefaciens SQ-2, previously isolated from a commercial watercress paste, was investigated for its potential in promoting rice growth in Pb/Al-contaminated acidic soil, especially when used in conjunction with corn straw biochar. Firstly, the physiological properties of rice were enhanced, with the activities of catalase and superoxide dismutase increasing by 162.5% and 162.9%, respectively. Additionally, the total phenolic and chlorophyll contents of rice increased by 17.6% and 83.7%, respectively. Secondly, the nutrient content of the rice rhizosphere soil was improved. In particular, nitrate nitrogen, available potassium, and sucrase were enhanced by 9.4%, 45.9%, and 466.8%, respectively. Moreover, SQ-2–biochar was demonstrated to have a notable capacity for removing Pb2+ and Al3+. The mineralization of Pb2+ and Al3+ was achieved through the use of SQ-2–biochar, as revealed by SEM-EDS, XRD, XPS, and FT-IR analyses, with the main precipitates being Pb3(PO4)2 and AlPO4. Functional groups such as C-O-C, C=O, N-H, P-O, and -O-H on the microbial surface were found to be involved in the biosorption process of Pb2+ and Al3+. In summary, SQ-2–biochar can effectively mineralize Pb2+ and Al3+, enhance the physiological properties of rice, and improve soil nutrients, thereby augmenting the antioxidant capacity, photosynthesis, and stress resistance of rice and ultimately promoting rice growth.